2020
DOI: 10.3390/vaccines8040779
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Risk Assessment for rVSVΔG-ZEBOV-GP, a Genetically Modified Live Vaccine for Ebola Virus Disease

Abstract: rVSVΔG-ZEBOV-GP is a live, attenuated, recombinant vesicular stomatitis virus (rVSV)-based vaccine for the prevention of Ebola virus disease caused by Zaire ebolavirus. As a replication-competent genetically modified organism, rVSVΔG-ZEBOV-GP underwent various environmental evaluations prior to approval, the most in-depth being the environmental risk assessment (ERA) required by the European Medicines Agency. This ERA, as well as the underlying methodology used to arrive at a sound conclusion about the environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 82 publications
(177 reference statements)
0
7
0
Order By: Relevance
“…Another example of clinical trials where measures to avoid contact with animals have been proposed involved the use of a recombinant chimeric Vesicular stomatitis virus, in which the VSV glycoprotein was replaced to abrogate neurotoxicity and pathogenicity [ 74 ]. As the OV were derived from a vector-borne virus causing significant disease in pigs, cattle and horses, instructions for avoiding contact with livestock for seven days following administration of the OV have been proposed [ 75 ].…”
Section: Shedding Analysismentioning
confidence: 99%
“…Another example of clinical trials where measures to avoid contact with animals have been proposed involved the use of a recombinant chimeric Vesicular stomatitis virus, in which the VSV glycoprotein was replaced to abrogate neurotoxicity and pathogenicity [ 74 ]. As the OV were derived from a vector-borne virus causing significant disease in pigs, cattle and horses, instructions for avoiding contact with livestock for seven days following administration of the OV have been proposed [ 75 ].…”
Section: Shedding Analysismentioning
confidence: 99%
“… 72 However, due to the urgent need to develop an effective COVID-19 vaccine when this programme was initiated, we expedited the development of VSV∆G-SARS-CoV-2 for IM injection by making use of the substantial nonclinical and clinical data associated with the ebolavirus Zaire vaccine ERVEBO®, which is delivered by the IM route. 14 , 15 , 85 Moreover, advancing a vaccine for administration by standard IM injection was well supported by immunogenicity and efficacy data produced here using the hamster model, as well as a full nonclinical safety assessment that was completed before advancing to human trials (unpublished data); thus, VSV∆G-SARS-CoV-2 #9 (called V590) was advanced and evaluated in a phase 1 clinical trial, 18 which showed that a single IM injection with V590 was safe but not sufficiently immunogenic to continue with the product development path based on a vaccine for IM injection. Some of the preclinical data presented here provide useful context for considering the basis for the low immunogenicity of the single IM dose of VSV∆G-SARS-CoV-2 #9 observed in the phase 1 clinical trial.…”
Section: Discussionmentioning
confidence: 99%
“…This ERA comprises a comprehensive case-specific assessment of the potential adverse environmental effects that could result from the characteristics of the specific GM viruses, the exposure of the receiving environments, and from the interactions with target or non-target organisms in these exposed environments. The ERA required by the EMA is considered to provide an in-depth and complex assessment [60].…”
Section: Considerations For the Assessment Of Environmental Effects O...mentioning
confidence: 99%